Poly(ethylene glycol) or poly(2-ethyl-2-oxazoline) – A systematic comparison of PLGA nanoparticles from the bottom up. (5th July 2020) - Dirauf, Michael; Grune, Christian; Weber, Christine; Schubert, Ulrich S.; Fischer, Dagmar
Graphical abstract: Highlights: PEtOx- b -PLGA was synthesized in a similar fashion as PEG- b -PLGA. Both polymer classes performed similarly during nanoformulation. As a consequence, a matching composition of PEtOx- b -PLGA was of utmost importance. PEtOx- b -PLGA could potentially substitute PEG- b -PLGA in nanoparticle formulation. Abstract: In times of drastically increasing numbers of scientific reports dealing with the drawbacks of poly(ethylene glycol) (PEG), the search of PEG alternatives has never been more urgent. This study describes a one–to–one comparison of poly(2-ethyl-2-oxazoline)- b -poly(lactic- co -glycolic acid) (PEtOx- b -PLGA) to commercial PEG- b -PLGA from the bottom up in order to verify the similarity of both polymer classes when applied in nanoparticle formulation processes. For this purpose, a library of block copolymers with molar masses (Mn ) ranging from 6500 to 60, 000 g mol −1 was synthesized via tin-(II)-ethyl hexanoate (SnOct2 ) catalyzed ring-opening polymerization (ROP) of lactide and glycolide utilizing PEtOx-OH as a macroinitiator in the melt. The PEtOx- b -PLGA polymers were adjusted in terms of molar mass, dispersity and lactide to glycolide ratio of the PLGA block. Nanoparticle formulations showed a similar behavior for both polymer libraries. Zeta potentials as well as hydrodynamic diameter measured by laser light scattering were in excellent agreement, demonstrating the eligibility of PEtOx- b -PLGA as an alternative to formulate "stealth" nanoparticles.